Additional notes on biting midges from the subtropical forest of northeastern Argentina (Diptera: Ceratopogonidae) - Ayala, Mahia M.; Spinelli, Gustavo R.; Funes, Amparo; Ronderos, María M. (Zootaxa, 2015)
Adult males and pupae of Culicoides guarani Ronderos & Spinelli and Parabezzia brasiliensis Spinelli & Grogan are fully described and illustrated with a modern criterium from material recently collected in the vicinities of the city of Posadas in Misiones province, Argentina. Both species are compared with their most similar congeners. Besides, Bezzia blantoni Spinelli & Wirth and B. brevicornis (Kieffer) are firstly recorded from Misiones province.